Rapid Stretch Injury to Peripheral Nerves: Biomechanical Results. Issue 1 (July 2019) - Mahan, Mark A; Yeoh, Stewart; Monson, Ken; Light, Alan
Abstract : BACKGROUND: : Although most adult brachial plexus injuries result from high‐speed mechanisms, no laboratory model has been created to mimic rapid‐stretch nerve injuries. Understanding the biomechanical response of nerves to rapid stretch is essential to understanding clinical injury patterns and developing models that mimic the clinical scenario. OBJECTIVE: : To assess the influence of rate, loading direction, and excursion of stretch injuries on the biomechanical properties of peripheral nerves. METHODS: : The sciatic nerves of 138 Sprague‐Dawley rats were dissected and subjected to rapid‐ and slow‐stretch methods. Maximal nerve strain, persistent deformation, regional strain variation, and location of nerve failure were recorded. RESULTS: : Nerve rupture was primarily determined by weight‐drop momentum >1 N/sec (odds ratio = 27.8, P < .0001), suggesting a threshold condition. Loading direction strongly determined maximal strain at rupture ( P = .028); pull along the nerve axis resulted in nerve rupture at lower strain than orthogonal loading. Regional variations in nerve compliance and rupture location correlated with anatomic zones. Nerve branch anatomy was the largest contributing factor on maximum strain and rupture location. Rapidly stretched nerves are characterized by a zone of elastic recovery, followed by inelastic response at increasing strain, and finally rupture. CONCLUSION: : The large variation in previous results for nerve strain at rupture can be attributed to different testing conditions and is largely due to loading direction or segment of nerve tested, which has significant clinical implications. Nerve stretch injuries do not reflect a continuous variability to applied force but instead fall into biomechanical patterns of elastic, inelastic, and rupture injuries.